IL-8 and IP-10 expression from human bronchial epithelial cells BEAS-2B are promoted by Streptococcus pneumoniae endopeptidase O (PepO) - Jiaqiong Zou; Long Zhou; Chunlan Hu; Peng Jing; Xiaolan Guo; Sulan Liu; Yan Lei; Shangyu Yang; Jiankang Deng; Hong Zhang (BMC Microbiology, 2017)
Abstract Background The bronchial epithelium serves as the first defendant line of host against respiratory inhaled pathogens, mainly through releasing chemokines (e.g. interleukin-8 (IL-8), interferon-induced protein 10 (IP-10) etc.) responsible for neutrophil or lymphocyte recruitment to promote the clearance of inhaled pathogens including Streptococcus pneumoniae (S. pneumoniae). Previous studies have shown that IL-8 expression is induced by pneumococcal virulence factors (e.g. pneumolysin, peptidoglycan-polysaccharides, pneumococcal surface protein A (PspA) etc.), which contributes to the pathogenesis of pneumonia. Whether other pneumococcal virulence factors are involved in inducing chemokines expression in epithelium is still unknown. Results We studied the effect of PepO, a widely expressed and newly discovered pneumococcal virulence protein, on the release of proinflammatory cytokines, IL-8 and IP-10, from human bronchial epithelial cell line BEAS-2B and identified the relevant signaling pathways. Incubation of BEAS-2B with PepO resulted in increased synthesis and release of IL-8 and IP-10 in a dose and time independent manner. We also detected the increased and sustained expression of TLR2 and TLR4 transcripts in BEAS-2B stimulated by PepO. PepO activation leaded to the phosphorylation of MAPKs, Akt and p65. Pharmacologic inhibitors of MAPKs, PI3K and IκB-α phosphorylation attenuated IL-8 release, while IP-10 production was just suppressed by inhibitors of IκB-α phosphorylation, PI3K and P38 MAPK. Conclusion These results suggest that PepO enhances IL-8 and IP-10 production in BEAS-2B in a MAPKs-PI3K/Akt-p65 dependent manner, which may play critical roles in the pathogenesis of pneumonia.